Serum electrolyte changes in senile cataract patients at tertiary care teaching hospital in Marathwada region, Maharashtra, India - Soni, Pravin N.; Chabada, Dhiraj S.; Wankhede, Sheetal U.; Soni, Seema P. (International Journal of Advances in Medicine, 2017)
Background: Cataract is one of the leading causes of blindness in developing countries. The most common type of cataract is senile cataract. The exact pathogenesis of cataract is not known, but it is believed that age, sex, radiation and serum electrolyte changes are important responsible risk factor. Rise in serum sodium level is responsible for formation of cataract. Potassium and chloride are not responsible factor for formation of cataract as that of serum sodium level. The purpose of this study is to estimate serum sodium and potassium in senile cataract patients, as compared to those without cataract. Methods: This study consists of 100 senile cataract patients and age matched 100 normal healthy individuals without cataract, serum electrolyte is measured by using an electrolyte analyzer. Results: In our study there is significant rise in serum sodium and chloride levels in cases compare to control group which is statistically significant. Serum potassium levels are in significant. Conclusion: We have concluded that serum sodium and chloride are important markers of senile cataract formation. Restrictions of salt in the diet delay the process of cataract formation.